Screening and Identification of the First Non-CRISPR/Cas9-Treated Chinese Miniature Pig With Defective Porcine Endogenous Retrovirus pol Genes - Ma, Yuyuan; Jia, Junting; Fan, Rui; Lu, Ying; Zhao, Xiong; Zhong, Yadi; Yang, Jierong; Ma, Limin; Wang, Yanlin; Lv, Maomin; Yang, Haiyuan; Mou, Lisha; et al. (Frontiers in Immunology, 2022)
Pig to human xenotransplantation is considered to be a possible approach to alleviate the shortage of human allografts. Porcine endogenous retrovirus (PERV) is the most significant pathogen in xenotransplantation. We screened for pigs that consistently did not transmit human-tropic replication competent PERVs (HTRC PERVs), namely, non-transmitting pigs. Then, we conducted whole-genome resequencing and full-length transcriptome sequencing to further investigate the sequence characteristics of one non-transmitting pig. Using in vitro transmission assays, we found 5 (out of 105) pigs of the Chinese Wuzhishan minipig inbred line that did not transmit PERV to human cells, i.e., non-transmitting pigs. Whole-genome resequencing and full-length transcriptome sequencing of one non-transmitting pig showed that all of the pol genes were defective at both the genome and transcript levels. We speculate that the defective PERV pol genes in this pig might be attributable to the long-term inbreeding process. This discovery is promising for the development of a strain of highly homozygous and genetically stable pigs with defective PERV pol genes as a source animal species for xenotransplantation.